SPECIFIC FEATURES OF THE EDUCATION SYSTEM IN EASTERN COUNTRIES (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article discusses the emergence of the education system of Eastern countries, the first pedagogical views. Also, special attention is paid to the specific features of the education system of Eastern countries, new reforms, opportunities, and achievements.